How Does Competition Affect the Performance of MFIs? Evidence from Bangladesh - Khandker, Shahidur R.; Koolwal, Gayatri B.; Badruddoza, Syed (World Bank, Washington, D.C., 2013)
Over the past 20 years, Bangladesh has witnessed strong competition among microfinance institutions. Using program-level panel data from 2005-2010, this paper studies the microfinance institutions' recent competitive roles in their pricing of products, targeting strategies and portfolio shifts, as well as their ability to recover loans. The findings do not support the view that newer microfinance institutions are less risk-averse in their targeting, or that increased borrowing among households due to microfinance institution competition has lowered recovery rates. There is also a considerable urban-rural distinction; although newer microfinance institutions tend to attract riskier clients in urban areas, the opposite is true in rural areas. Loan recovery rates are also the highest among the newest microfinance institutions for women in rural areas, suggesting that microfinance institutions may offer distinct products in these areas to attract better-risk clients. The portfolio of newer microfinance institutions also has a greater share of lending for agriculture, and fewer savings products.